Comparing health risks and musculoskeletal issues between professional and casual mobile esports players: a cross-sectional descriptive study in Jakarta - Kurniawan, Antonius Andi; Darusman, Kianti Raisa; Chesar, Theresia Indriani Prima; Azalia, Xarisa; Kholinne, Erica (Frontiers in Sports and Active Living, 2024)
Mobile gaming poses significant health risks, such as musculoskeletal (MSK) and eye problems, as players maintain the same posture for long periods. The objective of the current study is to describe the prevalence and assess the association of musculoskeletal and eye problems among professional gamers (PG) and casual gamers (CG) with their physical activity level and physical fitness. A total of 94 mobile-gaming athletes (43 PG, 51 CG) were prospectively recruited in this study. Descriptive analysis was performed for BMIs, fatigue scores, musculoskeletal problems profile, and eye problems profile. The associations between physical activity level, BMI, grip strength, flexibility, and MSK injury were tested with a Chi-square test. A total of 65.96% of the players experienced MSK complaints, with the shoulder (26.2%), neck (25.4%), and hand (21.3%) being the top three affected regions. This study also found ocular issues among the players, with eye fatigue (n=50) as the most frequent complaint. Differential outcomes were observed between the PG and CG groups regarding physical activity (p = 0.001) and flexibility (p = 0.02). Conversely, no statistically significant variances were detected between the PG and CG concerning musculoskeletal (MSK) disorder indicators (p = 1.000), body mass index (BMI) (p = 0.132), body fat (BF) percentage (p = 0.317), grip strength (p = 0.006 for the right side, p = 0.116 for the left side), or waist circumference (p = 0.680). Furthermore, a significant association was observed between physical activity and BMI (p = 0.029). Study results showed that two-thirds of players experienced MSK injury, with the most common complaints being neck, shoulder, hand, and wrist pain. All participants reported at least one eye problem, with the majority reporting multiple complaints. There were significant differences observed in physical activity and flexibility between the PG and CG groups; however, no correlation was found between musculoskeletal injury incidence and the players' physical fitness variables. This lack of correlation may be attributed to the relatively short career span of gamers.